Many (= All) are Called, But Few (= Not All) are Chosen - Meyer, Ben F. (New Testament studies, 1990)
The conviction that God is good, that he takes ‘no pleasure in the death of the wicked’ (Ezek 18. 23), that he ‘desires all men to be saved’ (1 Tim 2. 4), and that Christ ‘gave himself as a ransom for all’ (1 Tim 2. 4), belongs to the main thrust of Christian soteriology. Although there have been soteriological pessimists (Thomas Aquinas, the Angelic Doctor, was an optimist on the salvation of the angels, but a pessimist on the salvation of human beings) and optimists (Karl Barth construed Paul's universalist teleology as a flat guarantee of universal salvation), most Christians have had to content themselves with an affirmation of God's at least antecedently universal salvific will, with the hope for the salvation of many and even of all, and with a straightforward agnosticism respecting whether the finally lost will be ‘any’ or ‘many’ or something in between. But, in the word of Matt 22.14 (l.v. 20. 16), Jesus himself speaks, and he seems (a) to evoke election = predestination = salvation, (b) to reduce the number of the elect = predestined = saved to ‘few’, and (c) to suggest that the differentiation between the called and the elect is not the outcome of human acts but of divine decision. All three factors — final salvation is at stake, few are saved, and this by God's sovereign decision — say why this word has been a crux interpretum.